PENGARUH DISIPLIN BELAJAR DAN LINGKUNGAN TEMAN SEBAYA TERHADAP PRESTASI BELAJAR MAHASISWA PROGRAM STUDI AKUNTANSI DI UNIVERSITAS ISLAM MALANG, UNIVERSITAS ISLAM NEGERI MALANG, DAN UNIVERSITAS MUHAMMADIYAH MALANG - Lutfiyah Lutfiyah; Dwiyani Sudaryanti (Universitas Islam Malang, 2021)
The purpose of this study was to examine the significant effect of learning discipline and peer environment on student achievement in accounting study programs at the Malang Islamic University, the Malang State Islamic University, and the Malang Muhammadiyah University. The population in this study were students of the Faculty of Economics & Business UNISMA, UIN, UMM Accounting class 2018, the sampling was carried out as many as 280 students. This study uses a quantitative approach, in collecting using a questionnaire and data analysis using descriptive statistics and multiple linear regression. The results showed that there was a significant influence between learning discipline and peer environment on student achievement in the accounting study program at the Malang Islamic University, the Malang State Islamic University, and the 2018 Muhammadiyah University of Malang.Keywords: learning discipline and peer environment and student achievement